2010
DOI: 10.4317/medoral.15.e839
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative verrucous leukoplakia: A proposal for diagnostic criteria

Abstract: Proliferative verrucous leukoplakia (PVL) is a rare form of oral leukoplakia, which was first described in 1985 by Hansen et al. Since then, various published case series have presented PVL as a disease with aggressive biological behaviour due to its high probability of recurrence and a high rate of malignant transformation, usually higher than 70%. PVL is a long-term progressive condition, which is observed more frequently in women and elderly patients over 60 years at the time of diagnosis. Eventually, PVL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
136
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 32 publications
1
136
0
10
Order By: Relevance
“…In cases where it was difficult to evaluate whether the distance was within 1.5 cm due to post-operative scar formation or an irregular anatomy, the lesion was classified as a recurrent lesion. In line with the diagnostic criteria for proliferative verrucous leukoplakia (PVL) proposed by Cerero-Lapiedra et al (11), patients with multiple primary OSCC who previously had PVL were included.…”
Section: Methodsmentioning
confidence: 99%
“…In cases where it was difficult to evaluate whether the distance was within 1.5 cm due to post-operative scar formation or an irregular anatomy, the lesion was classified as a recurrent lesion. In line with the diagnostic criteria for proliferative verrucous leukoplakia (PVL) proposed by Cerero-Lapiedra et al (11), patients with multiple primary OSCC who previously had PVL were included.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin and eosin stained slides from the resection specimens, as well as any prior biopsy specimens, were reviewed for classification. Patients meeting criteria for proliferative verrucous leukoplakia (based on clinical and pathologic features described in the literature) were excluded [11,12]. Treatment and follow up information were gathered from the electronic medical The following criteria were used to classify tumors into Categories A, B, or C. Category A were pure VC cases showing the characteristic histopathologic features, such as thick, inward growing ribbons and nests with large epithelial cells having abundant glassy, eosinophilic cytoplasm, hyperkeratosis, broad pushing rete with or without chronic inflammation at the epithelial-stromal junction, and smooth stromal interface (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…5,8 Recent studies have demonstrated that the inclusion of benign alveolar ridge keratosis as a type of OL causes a deviation in the reported percentage of malignant transformation. However, when benign alveolar ridge keratosis is excluded from the OL group, the frequency of dysplasia transforming into squamous cell carcinoma increases from 18% to 25%.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…2 The etiology of OL is variable, and tobacco has been considered a risk factor in a large number of cases, while alcohol, as an independent risk factor, is still questionable. [2][3][4][5][6][7] The concept of malignant transformation of OL is quite controversial. Studies have indicated that there is a 36% chance of malignant transformation if the lesion exhibits dysplastic features.…”
Section: Introductionmentioning
confidence: 99%